Role of Vitamin D in the Treatment of Atopic Dermatitis - Limanda, Claudia Felicia; Gabriella, Gabriella; Bernadetta, Elvira; Hakim, Jackson; Tansuri, Verika Christabela (Indonesian Journal of Global Health Research, 2024)
Atopic dermatitis (AD) is a chronic and recurrent inflammatory condition that affects patients' quality of life. One alternative that has an anti-inflammatory effect on AD is vitamin D (25-hydroxyvitamin D (25(OH)D). Although the main treatment for AD uses drugs such as corticosteroids or immunosuppressants, the side effects caused are quite high. Therefore, the aim of this review This literature aims to find out more about the effectiveness of vitamin D against AD, so that it can be an alternative treatment option. Objective: To determine the role of vitamin D in the treatment of atopic dermatitis. Method: The research took database sources from Pubmed, Google Scholar, Science Direct, and Cochrane from 2014-2023 which were then selected based on the inclusion and exclusion criteria that had been created. A total of 17972 articles were found using the keywords ("Vitamin D" OR "Calciferol" OR "Calcitriol") AND "Atopic Dermatitis" AND ("Role" OR "Function") which then after screening, 16 articles were taken for this literature review. Results: AD is an inflammatory condition that is influenced by various factors. The severity of this disease can be assessed using SCORAD or EASI. AD patients generally have lower serum vitamin D levels and decreased SCORAD index. However, vitamin D supplementation in AD treatment varies according to each country and geographic region. Conclusions: Various studies have been conducted to review the effects of vitamin D supplementation on AD, but not all of them show significant effects. This is influenced by many factors, especially age, dosage, preparation, country and geographical area. So more in-depth research is needed on this matter.